Cellulose Synthase Complexes: Composition and Regulation - Lei, Lei; Li, Shundai; Gu, Ying (Frontiers in Plant Science, 2012)
This review is to update the most recent progress on characterization of the composition, regulation, and trafficking of cellulose synthase complexes. We will highlight proteins that interact with cellulose synthases, e.g. cellulose synthase-interactive protein 1 (CSI1). The potential regulation mechanisms by which cellulose synthase interact with cortical microtubules in primary cell walls will be discussed.